2015
DOI: 10.1007/s00294-015-0483-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and physiological effects of environmental UV radiation on fungal conidia

Abstract: Conidia are specialized structures produced at the end of the asexual life cycle of most filamentous fungi. They are responsible for fungal dispersal and environmental persistence. In pathogenic species, they are also involved in host recognition and infection. Conidial production, survival, dispersal, germination, pathogenicity and virulence can be strongly influenced by exposure to solar radiation, although its effects are diverse and often species dependent. UV radiation is the most harmful and mutagenic wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 180 publications
(112 citation statements)
references
References 218 publications
2
99
0
11
Order By: Relevance
“…Accordingly, many studies that evaluated the effect of UV radiation on entomopathogenic fungi have calculated the dose based on the Quaite-weighted irradiance rather than on the total irradiance (Fernandes et al 2007;Braga et al 2001a, d;Rangel et al 2004;Nascimento et al 2010). For a more detailed discussion on this subject, see Braga et al (2015) in this issue of Current Genetics.…”
Section: Seeking Fungal Isolates Naturally Tolerant To Uvmentioning
confidence: 98%
“…Accordingly, many studies that evaluated the effect of UV radiation on entomopathogenic fungi have calculated the dose based on the Quaite-weighted irradiance rather than on the total irradiance (Fernandes et al 2007;Braga et al 2001a, d;Rangel et al 2004;Nascimento et al 2010). For a more detailed discussion on this subject, see Braga et al (2015) in this issue of Current Genetics.…”
Section: Seeking Fungal Isolates Naturally Tolerant To Uvmentioning
confidence: 98%
“…Environmental conditions during conidiation affect the physiological properties, such as morphology, germination kinetics, and pathogenicity, of spores from other fungi [1720]. In addition, entomopathogenic fungi have demonstrated that virulence toward insect hosts, and conidial tolerance to heat and UV radiation, are greatly influenced by environmental conditions such as the medium, water activity, light illumination, and oxygen concentration, during conidia production [21,22]. Thus, environmental conditions appear to be key factors that affect fungal conidial properties; however, little is known about the impacts of temperature on the properties of the conidia of Aspergillus species, including the medically important pathogenic fungus A .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, most fungi show light‐induced expression of defense genes which protect against or repair such lesions, and formation of pigments which filter visible light and/or UV (Braga et al. ).…”
Section: Introductionmentioning
confidence: 99%